ANALISIS SKALA EKONOMI DAN EFISIENSI PADA INDUSTRI KERAJINAN KACA MOZAIK DI DESA TEGALLALANG KABUPATEN GIANYAR - Krismayanti, Anak Agung Mas; Indrajaya, I Gusti Bagus (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2021)
Existence of mosaic glass handicraft industry in Tegallalang Village faces problems hinder the development of small industrial businesses. This study aims (1) to analyze the effect of capital and labor simultaneously on the production of the mosaic glass handicraft industry (2) to analyze the effect of capital and labor partially on the production (3) to analyze the economies of scale in the production. (4) to analyze the level of capital and labor efficiency in the production. This study uses primary data with a number of samples taken as many as 60 business units, using saturated sampling techniques. Data collection methods used observation and in-depth interviews, and using multiple regression analysis. The results of the analysis in this study (1) capital and labor simultaneously have a significant effect on production. (2) each capital and labor variable has a partially positive effect on production. (3) economies of scale in the mosaic glass handicraft industry in Tegallalang Village, in a condition of increasing return to scale. (4) the level of efficiency in the use of capital and labor in the mosaic glass handicraft industry in Tegallalang Village, efficient condition and its use can still be improved. Keywords : Capital, Labor, Production, Economic Scale, Efficiency.